1982
DOI: 10.3109/01485018208990242
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Testosterone, Estradiol-17β, and 5α-Dihydrotestosterone on Inhibin Production by Sertoli Cells in Culture

Abstract: Inhibin activity in charcoal-extracted spent culture medium of Sertoli cells in Primary culture (CSCCM) was monitored by following the temporal inhibition of serum levels of luteinizing hormone (LH) and follicle-stimulating hormone (FSH) in normal adult male rats. Subcutaneous injection of CSCCM reduced LH and FSH levels within 15 min and maintained the inhibition up to 10 hr. No selective suppression of FSH was observed. The model was used to assess inhibin activity in CSCCM from Sertoli cell cultures incubat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
1

Year Published

1985
1985
2000
2000

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 7 publications
0
4
1
Order By: Relevance
“…Unlike in immature animals, in adults 10 ng DHT may increase the release of FSH-RF from day 82 onwards, resulting in raised serum FSH levels. On the other hand, DHT inhibits the release of inhibin by Sertoli cells in vitro (Nagendranath, Jose, Sheth & Juneja, 1982a). If this observation is con¬ sidered in relation to the present findings, it may be suggested that, unlike in immature animals, lOng DHT inhibits endogenous levels of inhibin from days 82 to 117, resulting in raised serum FSH levels.…”
Section: Discussioncontrasting
confidence: 40%
“…Unlike in immature animals, in adults 10 ng DHT may increase the release of FSH-RF from day 82 onwards, resulting in raised serum FSH levels. On the other hand, DHT inhibits the release of inhibin by Sertoli cells in vitro (Nagendranath, Jose, Sheth & Juneja, 1982a). If this observation is con¬ sidered in relation to the present findings, it may be suggested that, unlike in immature animals, lOng DHT inhibits endogenous levels of inhibin from days 82 to 117, resulting in raised serum FSH levels.…”
Section: Discussioncontrasting
confidence: 40%
“…This was particularly evident by the fact that studies from some laboratories showed a stimulatory effect of FSH on bioactive inhibin (10)(11)(12)(13)(14) while those from others showed no effect (14). Similarly, testosterone (T) was reported to stimulate (14) or suppress bioactive inhibin (15,16).…”
mentioning
confidence: 87%
“…These results provided indirect evidence for the hypothesis that inhibin is involved in the control of FSH secretion. However, the hormonal regulation of inhibin in vivo has not been investigated, although several in-vitro studies employ¬ ing Sertoli cells in culture have been reported (Steinberger, 1979(Steinberger, , 1981Nagendranath, Jose, Sheth & Juneja, 1982;Verhoeven & Franchimont, 1983). Recently we have validated an in-vitro bioassay using cultured rat anterior pituitary cells for the determination of inhibin content in rat testes (Au et al 1983).…”
Section: Introductionmentioning
confidence: 97%